Evaluation of village development index using geospatial analysis in determining inequality development - Ibrahim E.; Usman F.; Hamim S.A. (American Institute of Physics Inc., 2024)
The consequence of development, either in an urban or rural area, is still overcoming inequality. Governmental agencies and non-governmental organizations have given efforts to study the factors triggering the inequality by comparing different dimensions and looking for correlations between the factors to mitigate and solve this situation. Traditionally, using conventional statistical analysis, marginal solution, and action gave an appropriate solution. This paper presents a geospatial data analysis that is used to determine inequality in the rural area of a regional government development program. The study area in this paper is the Banyuasin Regency of South Sumatra Province. The inequality in this study was investigated from the village development index (IDM) yer 2018 and year 2019. The data was converted into geospatial information. Geospatial data analysis was conducted to map, explore, and cluster the information. From this study, the main factors that predominantly contributed to the inequality in the rural area of Banyuasin Regency are determined. The finding of this paper can be benefited in justifying appropriate actions and policies to balance development and address inequality. 2023 Author(s).